Law and economics toward social justice - Gold, Dana L. (Emerald, 2009)
This volume explores the relationship between law and economics principles and the promotion of social justice. By social justice, we mean a vision of society that embraces more than traditional economic efficiency. Such a vision might include, for example, a reduction of subordination and discrimination based on race, religion, gender, sexual orientation, age, disability or class; increased wealth dispersion throughout all sectors of society; a safe and healthy environment; worker rights; and, a flourishing political democracy. The volume chapters here fall into four main categories, Assumptions of Law & Economics; Law & Economics: Implications of Behavioralism; Economics and Corporate Governance: Finding the Holes; and, Gender, Class and Race: Implications of and Alternatives to the Dominant Economic Paradigm. In addition, most of the chapters invoke the lens of corporate law theory or the corporate context as part of their analysis of the intersection of economics and social justice.
Keywords: Social justice.; Economics -- Sociological aspects.; elektronické knihy; electronic books